Columnar to equiaxed grain transition of laser deposited Ti6Al4V using nano-sized B4C particles. (1st May 2021) - Meng, Xin; Min, Jin; Sun, Zhonggang; Zhang, Wenshu; Chang, Hui; Han, Yuanfei
Abstract: A new laser melting deposition (LMD) method was employed for Ti6Al4V to stimulate the columnar to equiaxed transition (CET) via adding 1 wt% ~ 5 wt% nano-sized B4 C particles. Results indicate that the grains were signifcantly refined from 600 μm to 11 μm with the increasing content of B4 C; When the B4 C content was 3 wt%, the B4 C/Ti6Al4V composite achieved CET; TiB and TiC reinforcements were produced by in-situ reaction between the Ti6Al4V and B4 C, which not only precipitated at the grain boundaries to restrict the grain growth, but also acted as nucleation sites to accelerate the non-spontaneous nucleation of β grains to achieve fine grain strengthening. Tensile tests show that adding 3 wt% B4 C particles results in a signifcantly increased yield strength (1235 MPa) and tensile strength (1310 MPa) and maintains a certain amount of ductility (2.4% elongation). And the epitaxial growth of β grains in the underlying deposited layer and the CET mechanism with successive layer-upon-layer deposition were analyzed. Highlights: Original β grains and α-lath are prompted to be equiaxed with the addition of B4 C. Crystallization routes in melt pool with B4 C different conents are studied. Epitaxial growth of the grains in TMCs is restricted, but promot CET of grains.